Analysis of the volatility of wind energy production in Romania applying the EGARCH model - Ioan-Cătălin Murărașu (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2023)
Purpose: The objective of the paper is to highlight the volatility of wind energy production, the renewable source of energy whose output is the most difficult to predict due to its dependence on climatic factors. The present research helps to analyze the risks assumed both by the producers who choose to invest in wind farms and the operator who has to balance the national energy system in case of production fluctuations. Many times, these risks are taken over, without their knowledge, by the final consumers who have to pay higher prices for the energy consumed. Design/methodology/approach: In this study, the EGARCH model was applied with the help of EVIEWS 12 software on a data series updated at least every 10 hours (1405 entries) regarding the evolution of wind energy production from January 2021 to January 2023. As a rule, the EGARCH model is used to analyse the volatility of indices in the financial field, but the present study, as well as others before, showed that it also fits perfectly in the case of renewable energy, the statistical tests applied to the results proving this fact. Findings: The results of the study show a GARCH term of 0.936, which points out a volatility comparable to some of the riskiest international stock indices. Research limitations/implications: This volatility is reflected through increases in balancing costs, ultimately borne by the energy consumers on the national market. Against this background, it is necessary to increase the stability of the national energy system, so that the balancing process would be less expensive and less dependent on imports. The solutions are varied - from the creation of stable non-polluting production capacities, such as the nuclear ones, to the thorough analysis of the characteristics of the areas where production systems from renewable sources are installed. It must be mentioned that the main limitation of this study is the long period considered, because the accuracy of the results could be better if the model was applied several times for data from consecutive, shorter periods. Originality/value: This study contributes to the theoretical identification of methods to forecast the volatility of renewable energy production and to highlight the vulnerabilities of increasing the share of this energy in the European energy mix. It tests the use of heteroscedastic models to estimate the volatility of the wind power supplied to the system, unlike most studies in the literature, which analyze the volatility of the energy market price. In addition, it proposes some solutions that could reduce or control this instability and ensure the regional energy security.
Keywords: F64; O13; P18; Q42; 330; EGARCH; renewable energy; volatility; balancing costs; wind power